The comparative susceptibility of commercial and Nigerian indigenous chicken ecotypes to Salmonella gallinarum infection (2013)
This study was to evaluate thè possible genetic resistance of exotic and indigenous chicks to Salmonella gallinarum. A total of 72 nine weeks-old chicks were used for thè study. The Fulani ecotype (Fulani smooth feathers - FSF), Yoruba ecotype (Yoruba smooth feathers - YSF), and thè Exotic breed (Nera Black) chicks were infected with a dose of S. gallinarum (8.3 x IO6 CFU) and were observed for 16 days. Evaluation of resistance was based on clinical signs, mortality, pathology, leukocyte count, bacterial count from liver and spleen of infected chicks. The highest peak for clinical signs in 5. gallinarum infected chicks coincides with highest mortalities recorded on day 11-12 dpi and bacterial count of both liver and spleen on day 8. The lymphocytes count declined on day 8 for all thè experimental chicks except for thè exotic breed. There was no significant difference between thè bacterial counts of thè different groups on day 8. In S. gallinarum infected chicks, 94.4% of all thè chicks showed clinical signs after infection, thè exotic breed showed a prolonged clinical signs while thè Yoruba ecotype showed thè least. 87.5%, 80.0% and 37.5% mortality were recorded in thè exotic breed, Fulani and Yoruba ecotypes respectively. The study showed that thè exotic chicken (Nera Black) was more susceptible to Salmonella gallinarum infection. It also indicated that within thè ecotypes in Nigeria, Fulani ecotype was more susceptible to Salmonella gallinarum infection than thè Yoruba ecotype. The lower clinical signs and mortality observed in Yoruba ecotype indicated a resistance of thè ecotype to 5. gallinarum infection.